Zoonoses and animal health: man, bird and beast - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Diseases passed from animals to humans cause untold damage to the lives and livelihoods of people living in ACP countries...